İslâm hukukuna göre borç ödemelerinde paradaki değer değişimi - Kundak, Oğuzhan (My University, 2024)
Bu tezde, para olaylarında para borçlarının nasıl ödeneceğine ilişkin hususlar ele alınmaktadır. Bu çerçevede paranın yürürlükten kaldırılması olan kesâd, piyasada bulunmaması olan inkıtâ ve değer değişimleri olan raḥs, ġalā, tağşiş, enflasyon, deflasyon, devalüasyon ve revalüasyon olaylarının para borçlarındaki ödemeye etkisi İslâm hukuku açısından incelenmiştir. Klasik ve modern dönem fıkıh ve iktisat literatüründeki para ve para olaylarındaki esaslar, problemler ve görüşler, fıkıh ve iktisat perspektifiyle teorik ve tarihsel gelişim çerçevesinde değerlendirilmiştir. Klasik döneme dair yapılan araştırmada kesâd, inkıtâ, raḥs ve ġalā sebebiyle hilkaten paralarda inkıtâ hali hariç genellikle misle; ıstılahî paralarda genel görüş olmamakla birlikte müftâbih görüş olarak tüm hallerde kıymete itibar edildiği görülmüştür. Modern dönemde yeni bir şey olan banknotların ve iktisat literatürüne ait kavramlar olan enflasyon, deflasyon, devalüasyon ve revalüasyonun İslâm hukukuna göre sistematik olarak temellendirilemediği, dolayısıyla başta enflasyonda olmak üzere kâğıt para borçlarının ödenmesindeki yaklaşımların tutarlılık arz etmediği gözlemlenmiştir. Bu bağlamda banknotların İslâm hukukuna göre ıstılahî olarak değer ölçüsü niteliği taşıdığı, tedavüle sürülüş şekline göre hükme tâbi olması gerektiği ve diğer paralardan farklı şekilde kâğıt para olarak müstakil bir para olduğu tespit edilmiş; enflasyon ve deflasyonun klasik fıkıh literatüründeki raḥs ve ġalānın bir çeşidi, devalüasyon ve revalüasyonun tağşişin kendisi olduğu gözlemlenmiştir. Sonuç olarak bu çalışma, temsili mahiyette tedavüle sürülen kağıt paraların hilkaten para hükmünde olmasıyla kesâd ve inkıtâ hallerinde kıymete; enflasyon ve deflasyonda misle; itibari olarak tedavüle sürülen kâğıt paraların ise ıstılahî para hükmünde olmasıyla tüm hallerde mutlak olarak kıymete itibar edilmesinin literatürde ve uygulamada görülen farklı yorum ve çözüm arayışları içerisinde öne çıkan bir yaklaşım olabileceğini temellendirmektedir.

This thesis deals with the issues of how to pay money debts in money events. In this framework, the effects of kesād, which is the abolition of money, inkıtā, which is the absence of money in the market, and raḥs, ġalā, taghshish, inflation, deflation, devaluation and revaluation, which are the changes in value, on the payment of money debts are examined in terms of Islamic law. The principles, problems and views on money and money events in the classical and modern period fiqh and economics literature are evaluated within the framework of theoretical and historical development from the perspective of fiqh and economics. In the research conducted on the classical period, it has been observed that in the case of hilqatan money due to kesād, inkıtā, raḥs, and ġalā, the mithl (fungible) was generally accepted, except in the case of inkıtā, and in the case of idiomatic money, although there was no general opinion, the value was accepted in all cases as the muftābih opinion. It has been observed that banknotes, which are something new in the modern period, and inflation, deflation, devaluation and revaluation, which are concepts belonging to the economic literature, cannot be systematically justified according to Islamic law, and therefore, the approaches to the payment of paper money debts, especially inflation, are not consistent. In this context, it has been determined that banknotes are a measure of value in Islamic law, that they should be subject to judgement according to the way they are put into circulation, and that they are an independent money as paper money unlike other money; it has been observed that inflation and deflation are a type of raḥs and ġalā in classical fiqh literature, and devaluation and revaluation are taghshish. As a result, this study argues that, since the paper money circulated in the form of representational currency is deemed to be money by hilqatan money the value should be considered in the cases of kesâd and inkıtâ, mithl should be considered in cases of inflation and deflation, and since the paper money circulated in the form of fiat currency is deemed to be terminological money in all cases, absolutely value should be considered in all cases, which may be a prominent approach among the different interpretations and search for solutions seen in the literature and practice.
Change in value of money in debt payments according to Islamic law
Keywords: Banknotes; Borç; Debt; Deflasyon; Deflation; Enflasyon; Ġalā; Inflation; Islamic Economics; Islamic law; İslam hukuku; İslâm Hukuku; İslâm İktisadı; Kağıt Para; Raḥs